Enhancing the nutritional and textural properties of gluten-free shortbread biscuits: The potential of white-fleshed sweet potato flour blended with corn starch - Ozgolet, Muhammed; Belkacemi, Louiza; Arici, Muhammet (WILEY, 2025)
Sweet potato flour (SPF) is a promising gluten-free alternative to wheat flour, though it affects the texture of shortbread biscuits. This study aimed to evaluate the potential of white-fleshed SPF, both peeled (PSP) and unpeeled (USP), as an alternative to soft wheat flour in the production of gluten-free shortbread biscuits. Specifically, this study aimed to assess how blending SPF with corn starch influences the nutritional, physical, and textural properties of shortbread biscuits. For this purpose, shortbread biscuits (B) were prepared using PSP or USP white-fleshed SPF alone (B100) or in a 1:1 mixture with corn starch (B50). Control shortbread biscuits were made from 100% wheat flour (WB) or 100% corn starch (SB). All the samples were analyzed for their proximate composition, mineral, polyphenol, and flavonoid contents. The physical and textural properties were assessed, in addition to their in vitro glycemic index (GI). Results showed that unpeeled SP biscuits (USPB100) had the highest fiber (6.63%), minerals (1.99%), polyphenols (88.85 mg gallic acid equivalent/100 g), and flavonoids (213.96 mg quercetin equivalent/100 g). PSP and USP increased hardness but improved mineral content (Na, Ca, Mg, Fe, and Zn) compared to controls. Furthermore, all the shortbread biscuits made with both PSP and USP flours, totally or mixed with corn starch, recorded an estimated GI lower than the wheat and corn starch-based shortbread biscuits. In summary, blending SPF with corn starch permitted the development of gluten-free shortbread biscuits with enhanced textural and physical properties while achieving satisfactory nutritional quality.
Keywords: Algerian cultivar; corn starch; glycemic index; sweet potato; unpeeling; QUALITY CHARACTERISTICS; DIETARY FIBER; BY-PRODUCTS; COOKIES; DIGESTIBILITY; VALUES; Food Science & Technology